Encapsulating Ag nanoparticles into ZIF-8 as an efficient strategy to boost uranium photoreduction without sacrificial agents. Issue 15 (7th April 2021) - Jiang, Pengyan; Yu, Kaifu; Yuan, Haibo; He, Rong; Sun, Mengping; Tao, Feng; Wang, Liangbing; Zhu, Wenkun
Abstract : Hot electrons generated over Ag nanoparticles were transferred to ZIF-8 to efficiently reduce adsorbed U(vi ). The coherence between adsorption sites and electron acceptors directly contributes to the excellent U(vi ) enrichment performance. Abstract : Photoreduction of hexavalent uranium (U(vi )) opens up a novel avenue to promote the kinetics, capacity, and selectivity during uranium removal, where organic molecules are generally employed as the sacrificial agents to capture photo-generated holes. Unfortunately, the introduction of sacrificial agents not only increases the cost of uranium removal, but also results in secondary chemical pollution. Therefore, developing highly active photocatalysts to efficiently reduce U(vi ) to U(iv ) without any sacrificial agents is urgently desired, but remains a great challenge. Herein, we have successfully developed highly active and stable photocatalysts for U(vi ) photoreduction without any sacrificial agents by encapsulating Ag nanoparticles into zeolitic imidazolate framework-8 (Ag/ZIF-8). Impressively, Ag/ZIF-8 exhibited unexpected U(vi ) removal performance in U(vi ) solutions with different pH values, concentrations, and co-existing ions. Even under the irradiation of natural sunlight, more than 85.8% of U(vi ) was enriched via Ag/ZIF-8, indicating remarkable potential in the practical applications in environmental protection. Further mechanistic studies revealed that hot electrons generated over Ag nanoparticles were transferred to ZIF-8 to efficiently reduce adsorbed U(vi ), directly contributing to the excellent removal capacity of Ag/ZIF-8 towards uranium enrichment.